INCREASING STUDENTS' SPEAKING SKILL THROUGH FISHBOWL - Sara Wati; Farnia Sari (Program Pendidikan Bahasa Inggris Universitas Tridinanti, 2023)
TThis study was intended to find out whether or not there was a significant influence on speaking achievement of the eighth-grade students of SMP Utama Bakti Palembang who were taught by using the fishbowl technique and those who were not, and there was the significant difference in speaking achievement between the eighth-grade students of SMP Utama Bakti Palembang who were taught by using fishbowl technique and those who were not. The quasi-experimental method was used to conduct the study. The population of this study was the eighth-grade students of SMP Utama Bakti Palembang in the academic year of 2020/2021. In this study, the sample was taken using the purposive sampling technique. In this study, the sample was taken from the population, and they would be divided into two classes. VIII A was an experimental group with a total of 23 students and VIII B was a control group with a total of 23 students. The results showed that the value significance of 0.001 was higher than the value significance of 0.05. While the value of t-obtained (3.592) was higher than t- table (2.079) with a degree of freedom was 44. In other words, there was a significant difference in speaking achievement between the eighth-grade students of SMP Utama Bakti Palembang who were taught by using the fishbowl technique and those who were not.